2001
DOI: 10.1002/ajh.1084
|View full text |Cite
|
Sign up to set email alerts
|

p53, Mdm2, and c‐Myc overexpression is associated with a poor prognosis in aggressive non‐Hodgkin's lymphomas

Abstract: The expression of p53, p21/WAF-1, Mdm2, c-Myc, and proliferating cell nuclear antigen (PCNA) proteins was examined by the immunohistochemistry of paraffin-embedded tissues of 62 patients with aggressive non-Hodgkin's lymphomas (NHL) and correlated to clinical data. Expression of p53, p21/WAF-1, Mdm2, and c-Myc protein was observed in 17 out of 62 cases (30%), 25 out of 60 (42%), 13 out of 44 (30%), and 39 out of 51 (76.5%), respectively. The p53 + /p21WAF-1 phenotype, which is more frequently found in p53 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
1
27
1
2
Order By: Relevance
“…c-Myc is overexpressed in numerous cancers, including prostate, gynecological, lung, pancreatic, breast, and colon cancers, B-cell lymphoma, and leukemias. Alterations in c-Myc often are associated with cancer aggressiveness and poor treatment prognosis (Fleming et al, 1986;Nesbit et al, 1999;Pagnano et al, 2001;McNeil et al, 2006). It has been estimated that approximately one-seventh of cancer deaths in the United States per year can be associated with tumors that have changes in the c-Myc gene or its expression (Dang, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…c-Myc is overexpressed in numerous cancers, including prostate, gynecological, lung, pancreatic, breast, and colon cancers, B-cell lymphoma, and leukemias. Alterations in c-Myc often are associated with cancer aggressiveness and poor treatment prognosis (Fleming et al, 1986;Nesbit et al, 1999;Pagnano et al, 2001;McNeil et al, 2006). It has been estimated that approximately one-seventh of cancer deaths in the United States per year can be associated with tumors that have changes in the c-Myc gene or its expression (Dang, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Results of expression analyses using Northern blot (Hernandez et al, 1999), in situ hybridization (Greil et al, 1991), and immunohistochemistry (IHC) (Chang et al, 2000;Pagnano et al, 2001) coincide in showing that c-myc overexpression is a common observation in BL and DLBCL. Despite this, there is striking variability in the reported c-myc protein cellular localization and intensity of c-myc expression in reactive and tumoral lymphoid tissue (Chang et al, 2000;Jack et al, 1986;Loke et al, 1988;Pagnano et al, 2001). Despite the significant role that c-myc seems to play in lymphomagenesis, the difficulties for demonstrating c-myc expression at the protein or RNA level has impeded our gaining a deeper understanding of the mechanism regulating c-myc expression and the identification of c-myc targets in lymphoma tumoral specimens.…”
mentioning
confidence: 96%
“…Furthermore, regulatory elements of promoters and enhancers of Ig and c-myc genes have been shown to contribute to this deregulation (Gerbitz et al, 1999;Ji et al, 1994;Kanda et al, 2000;Madisen and Groudine, 1994). Results of expression analyses using Northern blot (Hernandez et al, 1999), in situ hybridization (Greil et al, 1991), and immunohistochemistry (IHC) (Chang et al, 2000;Pagnano et al, 2001) coincide in showing that c-myc overexpression is a common observation in BL and DLBCL. Despite this, there is striking variability in the reported c-myc protein cellular localization and intensity of c-myc expression in reactive and tumoral lymphoid tissue (Chang et al, 2000;Jack et al, 1986;Loke et al, 1988;Pagnano et al, 2001).…”
mentioning
confidence: 99%
“…The other four microRNAs encoded by these clusters, had P values of 0.067,0.087, cluster is encoded at the 13q31 locus, a region commonly amplified in lymphomas and ectopic expression of miR-17-92 greatly accelerated lymphogenesis in a murine model (He et al 2005). Moreover, direct binding of the c-myc protein up-regulates miR-17-92 expression (O'Donnell et al 2005) and overexpression of c-myc has been demonstrated in the majority (66.6%) of DLBCL cases (Aref et al 2004), which has also been associated with poorer outcome (Pagnano et al 2001). An increased level of this cluster in DLBCL compared to FL is consistent with a more aggressive clinical phenotype of DLBCL.…”
Section: Microrna Expression Is Distinct Between Dlbcl and Flmentioning
confidence: 99%